Implementation of a Microbiological Surveillance Protocol in a Portuguese Tertiary Care Academic Endoscopy Unit - Cristiana Monteiro; Jorge Lima; Tiago Ribeiro; Maria Helena Gonçalves; Natália Gonçalves; Carina Oliveira; Liliana Soares; Ana Carvalho; Filipe Vilas-Boas; Maria Manuela Ribeiro; Guilherme Macedo; Sónia Barros (GE: Portuguese Journal of Gastroenterology, 2024)
Introduction: International societies recommend microbiological surveillance of endoscopes to reduce the incidence of endoscope-associated infections, particularly for duodenoscopes. However, surveillance protocols are not internationally standardized, both regarding sample collection, processing, and culture. This study aims to provide a framework protocol encompassing the experience of a tertiary large volume endoscopy center and the microbiology laboratory for collecting and culturing of endoscope samples for microbiological surveillance. Methods: A sample collection and processing protocol was designed as a result of a cooperation between the Endoscopy Center of the Gastroenterology Department and the Microbiology Laboratory of the Department of Clinical Pathology. This protocol reflects international recommendations in this topic and the human and technological resources of the involved departments. Results: The established protocol for collecting samples varies according to the type and model of endoscope. The specimens are collected as sterile saline liquid samples, as well as swabs (with and without transport media). Together with the collection of samples from the endoscope, samples from the final rinse water as well as the water bottle are also collected. For duodenoscopes and curvilinear echoendoscopes, we perform microbiological surveillance every 3 months; for gastroscopes and colonoscopes, at least, once a year; and for specific endoscopes, such as the pediatric or dual-channel therapeutic endoscopes, enteroscopes, or radial echoendoscopes, every 6 months. Conclusion: Endoscopy units should have detailed protocols for microbiological surveillance of endoscopes. These protocols should be drawn up by a multidisciplinary team that includes endoscopy nurses, gastroenterologists, microbiologists, and the antimicrobial stewardship team, following international recommendations, adapted to each institution resources.